Evening Crowd at Kirmser's : A Gay Life In The 1940S - Brown, Ricardo J. (Book collections on Project MUSE., 2001)
The Evening Crowd at Kirmser's is a compelling memoir of the author's experiences as a young gay man during the 1940s. In an engaging and open writing style, and through stories both humorous and tragic, Brown introduces us to the companions and friends he met at Kirmser's, a working-class bar in downtown St. Paul that became an unofficial home to gay men and lesbians at night. "Whimsical, insightful, and compellingly readable, Ricardo Brown's memoir offers a remarkable portrait of the life gay men built for themselves after the Second World War in small cities far from the coastal meccas of g.